Effectiveness of a Nutritional Education Intervention Program for Reducing Anemia in Pregnant Women of Western Nepal: A Hospital-Based Study - Sakai, Hiroko; Lee, Kumsun; Thapa, Yoko Oda; Kawata, Rina; Iwakuni, Akiko; Adhikari, Rajesh; Bhandari , Tulsi Ram (Journal of Health Promotion, 2024)
The anemia rate among pregnant Nepalese women remains high and has not significantly declined over the past 20 years. Thassess the effectiveness of a nutritional intervention program for reducing anemia in pregnant women. We conducted an intervention study among pregnant women visiting Western Regional Hospital in Pokhara, Nepal, from March 2019 to March 2020. We involved 138 participants in this study and divided them into three groups- education, distribution, and control. Hemoglobin levels were evaluated before and after the intervention. This study revealed that the mean hemoglobin values after the intervention were 11.65 ± 0.59 mg/dL in the education group, 11.15 ± 1.08 mg/dL in the distribution group, and 11.14 ± 1.19 mg/dL in the control group. The changes in hemoglobin levels were 1.40 ± 0.84 mg/dL in the education group, 0.96 ± 1.21 mg/dL in the distribution group, and 0.87 ± 1.11 mg/dL in the control group. The difference in the change in hemoglobin levels among the three groups was statistically significant. In conclusion, anemia during pregnancy can be effectively reduced through individual nutritional counseling using visual educational materials. Therefore, there is an urgent need to develop a national standard model of a nutritional education protocol for maternal women combined with training programs for maternal healthcare workers to upgrade their nutrition counseling skills.